436 COMBINING THE SRC INHIBITOR AZD0530 WITH IONIZING RADIATION YIELDS ADDITIVE EFFECTS WITHOUT MODULATION OF PHOSPHOSITES ON SRC, EPIDERMAL GROWTH FACTOR RECEPTOR, OR MITOGEN-ACTIVATED PROTEIN KINASE. (1st January 2006) - Rothschild, B. L.; Frederick, B.; Helfrich, B.; Weed, S. A.; Shim, A. H.; Song, J.; Raben, D.
Abstract : The Src family of proteins are cytoplasmic tyrosine kinases that play an important role in oncogenesis. In particular, members of this family have been shown to regulate cellular migration, proliferation, and differentiation. While Src plays this role in normal cells, some malignancies implicate the kinase in abnormal attachment, motility, and angiogenesis. There are currently several Src kinase inhibitors with oral bioavailability undergoing clinical investigation, including AZD0530. The purpose of this abstract is to report preliminary in vitro data investigating the role of AZD0530 both alone and in combination with radiotherapy. Cells growing in log phase were subjected to a 6-day proliferation assay with drug doses ranging from 0 to 20 μM and ionizing radiation doses ranging from 0 to 6 Gray. Four lung and four head and neck squamous cell carcinoma lines fell into sensitive or resistant subsets with AZD0530 IC50 's clustering around 1 μM or 10 μM, respectively. When combined with radiation, AZD0530 showed additive but not synergistic effects over a wide range of dose treatments using the Chou-Talalay median effect methods of calculating combination indices. Furthermore, lysates from cells treated with either the IC50 of inhibitor for 24 hours or radiation at 2 Gy were subjected to Western blot analysis to elucidate mechanisms. Under the conditions above, we observed no selective down-regulation of phospho-Src with AZD0530. While ionizing radiation has been shown to amplify pEGFR as well as VEGF in various cancer models, single-dose radiation did not appear to modulate phospho-Src activity either. In addition, after treatment with AZD0530 for 24 hours, we observed no down-regulation in several important growth factor pathways. In particular, we did not observe a decrease in phosphorylation on Src itself, on EGFR, or on MAPK. Src kinase has been shown previously to directly activate cortactin, an actin-associated protein involved in cell motility. In this regard, subsequent blots did show robust down-regulation of phospho-cortactin. Because AZD0530 exhibited a clear effect in the proliferation assays, yet we observed no modulation of the growth pathways, our future studies will investigate these pathways at different time points and with fractionated radiation. While cortactin down-regulation might explain decreased cell motility and invasion, its currently understood function cannot fully account for the observed anti-proliferative effects of AZD0530.